Variability of tropical cyclone rainfall volume in the Philippines. (22nd February 2022) - Bagtasa, Gerry
Abstract: This study investigates the variability of tropical cyclone (TC)‐induced rainfall volume and its relation to the total rainfall in the Philippines. Of the total 1, 843 TCs that formed in the western North Pacific (WNP) basin from 1951 to 2020, 983 (53%) and 1, 253 (68%) TCs directly and indirectly, respectively, contributed 23.3% of the total rainfall on Philippine landmass. Total seasonal rainfall is negatively correlated with El Niño–Southern Oscillation (ENSO) (February–May [FMAM] r = −0.71 and October–January [ONDJ] r = −0.77) except for the boreal summer months of June–September (JJAS) where no correlation was observed. Similarly, TC rain also shows a negative but weaker correlation with ENSO (FMAM r = −0.23 and ONDJ r = −0.33) except for JJAS, despite JJAS season having the highest TC rain contribution. Nevertheless, all top 90th percentile TC rain years occurred during La Niña and ENSO‐neutral years, similar to the total rain. Rainfall volume from individual TCs depends mainly on its rain duration and the area of land affected. There are no significant trends found in annual and seasonal TC rainfall, but the frequency of extreme TCs with rainfall volume in the upper 95th percentile is dropping by 10%·decade −1 . Annual TC rain volume is most correlated with TC landfall frequency ( r = 0.81). Despite the influence of ENSO on TC activity and tracks in the NWP region, the results in this study suggest that the use of the ENSO Niño3.4 index alone may not be enough for seasonal TC rainfall forecasts. Abstract : TC rain contributes 22.3% to total rainfall volume of the Philippines. Total and TC rainfall are both significantly correlated to the Niño3.4 index in FMAM and ONDJ seasons. Wet (dry) TC rain anomaly has higher chance of occurring during La Niña (El Niño) year. Extreme TC rain volume depends on how vast the rain area and how long rain duration are.